What's in a logo? The impact of complex visual cues in equity crowdfunding - Mahmood, Ammara; Luffarelli, Jonathan; Mukesh, Mudra (Journal of Business Venturing, 2019)
Visual cues are pervasive on crowdfunding platforms. However, whether and how low validity visual cues can impact the behavior of backers remains largely unknown. In this article, we propose a disfluency-based heuristic framework for understanding the influence of low validity visual cues on equity crowdfunding platforms. Drawing on processing fluency theory and visual heuristics, we propose that backers often automatically process visual cues, and that the subjective experience of ease/difficulty with which backers perceptually process low validity visual cues serves as a heuristic and informs their perceptions of early-stage entrepreneurial ventures. We test our propositions focusing on logos (low validity visual cues that are particularly salient and ubiquitous on equity crowdfunding platforms) and logo complexity (a fundamental characteristic of logo design and established antecedent of processing disfluency). We contend that logo complexity can be interpreted by backers as a signal of venture innovativeness because more (vs. less) complex logos are more difficult to process, and thus, feel less familiar and more unique, original, and novel to backers. Since backers often value innovativeness, we further contend that logo complexity can positively impact backers' funding decisions. We find support for our framework and propositions using a multimethod approach comprising three studies: one survey, one field study, and one experiment. Theoretical contributions and managerial implications are also discussed.